Social-spatial network structures and community ties of egocentric sex and confidant networks: A Chicago case study. (December 2021) - Kolak, Marynia A.; Chen, Yen-Tyng; Lin, Qinyun; Schneider, John
Abstract: Exploring how sexual and confidant networks overlap spatially and socially could facilitate a better understanding of sexually transmitted infection risk, as well as help identify areas for interventions. This study aims to examine how a sexual and peer-affiliate network is impacted or shaped by interconnected social relationships and spatial patterns. We used data collected from a sample of 618 young black men who have sex with men (YBMSM) and transgender women in Chicago (2013–2014) that includes partner and confidant links, geolocations, and pre-exposure prophylaxis (PrEP) awareness. We spatialize different types of social networks and examine joint social-spatial community ties to both identify and differentiate social-spatial behavioral patterns. We explore the spatial structures of the social network by comparing ego-alter network residence patterns, visualizing ego-alter community ties in aggregate, and grouping different types of dyad relationships based on their spatial structure. Findings showed overlapping social and sexual networks. Egos with partners residing in more resourced communities furthest away, with wider alter-ego power differentials, also tended to be at greatest risk. Identifying the social-spatial structures of community ties is critical to enhance our understanding of the spatial context of social relationships, and further distill risk heterogeneity in vulnerable populations within an equitable health framework. Highlights: Exploring social-spatial networks with GIScience could help us understand STI risk. We spatialize different HIV-vulnerable social networks and examine community ties. Social and sexual networks overlapped, though sexual networks extended further. Egos with alters furthest away had wider power differentials, and may be at risk. Identifying social-spatial structures of community ties is innovative and useful.